Violence against nurses in the southern region of Malawi - Chimwemwe Kwanjo Banda; Pat Mayers; Sinegugu Duma (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2016)
Purpose: To investigate and describe the nature and extent of violence against nurses and the perceived effects thereof on nurses in the southern region of Malawi. Methods: A descriptive, cross-sectional study in which 190 questionnaires were sent out to nurses from five facilities, 112 were returned completed (60% response rate). The five facilities included two central hospitals, one psychiatric hospital and two health care centres. Results: 86% of the respondents agreed that violence against nurses is a problem in Malawi. The prevalence of violence for the five facilities in the preceding 12 months was 71% (CI 61%–79%) and was highest at the psychiatric hospital (100%). The types of violence experienced include verbal abuse (95%), threatening behaviours (73%), physical assaults (22%), sexual harassments (16%) and other (3%). Perpetrators of violence were: patients (71%); patients' relatives (47%); and work colleagues (43%). Nurses reacted to incidents of violence by reporting to managers, telling their friends, crying, retaliating, or ignoring the incident. Most (80%) nurses perceived that violence has psychological effects on them, which consequently affects their work performance and make them lose interest in the nursing profession. Conclusions: Workplace violence against nurses exists in Malawi and it affects nurses psychologically; may result in poor work performance; and may be a causative factor in the attrition of nurses from the nursing profession. The study recommends that health facilities should adopt policies aimed at minimizing violence against nurses to create motivating and safe working environment for nurses.